Perspektif Masyarakat Pengguna BPJS Kesehatan mengenai Kebijakan Kelas Rawat Inap Standar (KRIS) - Pramana Pramana; Chairunnisa Widya Priastuty (Jurnal Jaminan Kesehatan Nasional, 2023)
The Republic of Indonesia's Government established BPJS Kesehatan as a public legal organization to organize the national health insurance program. The shift in the clustering policy of inpatient classes to Standard Inpatient Classes (KRIS) is one important adjustment implemented by the Government of Indonesia as part of a series of changes and improvements in regulations of the National Health Insurance (JKN). This change in KRIS raises the question of whether the existence of KRIS is adequate to meet the demands of the community after being acclimated to class-based inpatient facilities. To collect relevant information from the general public, this study uses a qualitative approach using a case study methodology. This study takes place in Klaten Regency and Yogyakarta Special Region Province based on a number of factors and considerations. Purposive sampling approach and in-depth interviews were used in this study to acquire data from four informants who represented various preset criteria. This study concluded that the acceptance of the community of active users of BPJS Kesehatan from each class at the research site related to the KRIS policy plan was relatively high. Furthermore, the study indicated that a thorough campaign is required as part of efforts to adopt KRIS based on the characteristics of the community and taking geographical and demographic variances into account